Pengaruh Penerapan Tarif Tunggal Pajak Penghasilan Badan terhadap Indikasi Penggelapan Pajak - Putra, Bramastia Candra; Qibthiyyah, Riatu M. (UI Scholars Hub, 2019)
This paper investigates the difference effects of progressive rate and single rate implementation on corporate income tax to tax evasion indication. Using firm level data of tax audit results as a measure of tax evasion indication for six years observations. The empirical results from the sample data show that the implementation of single rate on corporate income tax reduces the tax evasion indication. In addition, the results show that the higher the marginal income tax rate, the higher the tax evasion indication.